2000
DOI: 10.1046/j.1469-8137.2000.00745.x
|View full text |Cite
|
Sign up to set email alerts
|

Water relations and carbon gain are closely related to cushion size in the moss Grimmia pulvinata

Abstract: The present study of structural and physiological changes during the development of the cushion moss, Grimmia pulvinata, quantifies the size-dependence of various parameters of water relations such as changes in surface : volume ratio (S\V ) or water loss rates, and also measures net CO # gas exchange in the light and the dark. Larger cushions had lower S\V values than smaller ones and featured lower rates of area-based evapotranspiration, owing to higher boundary-layer resistance, but did not differ in relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 22 publications
4
67
0
Order By: Relevance
“…Evaporation from bryophyte leaves is controlled by diVusion through boundary layers adjacent to plant surfaces, as in vascular plants (Campbell and Norman 1998). However, (1) the general absence of stomata mean that the boundary layer is the major impediment to water loss (Proctor 1980) and (2) bryophyte cushion size and surface roughness control boundary layer thickness-and thus water relations and carbon gain (Zotz et al 2000)-as the small bryophyte leaves lie entirely within the cushion's laminar boundary layer at low to moderate wind speeds (Rice and Schneider 2004). Thus, in most conditions the bryophyte colony surface functions as a single "leaf" lacking an outer epidermis (Proctor 2000), enabling the bryophyte to maintain a large leaf area, while paying a smaller penalty in water loss than would most vascular plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaporation from bryophyte leaves is controlled by diVusion through boundary layers adjacent to plant surfaces, as in vascular plants (Campbell and Norman 1998). However, (1) the general absence of stomata mean that the boundary layer is the major impediment to water loss (Proctor 1980) and (2) bryophyte cushion size and surface roughness control boundary layer thickness-and thus water relations and carbon gain (Zotz et al 2000)-as the small bryophyte leaves lie entirely within the cushion's laminar boundary layer at low to moderate wind speeds (Rice and Schneider 2004). Thus, in most conditions the bryophyte colony surface functions as a single "leaf" lacking an outer epidermis (Proctor 2000), enabling the bryophyte to maintain a large leaf area, while paying a smaller penalty in water loss than would most vascular plants.…”
Section: Discussionmentioning
confidence: 99%
“…These few studies have generally measured the leaf area of individual samples (Proctor 2000;Rice and Schneider 2004;Williams and Flanagan 1998;Zotz et al 2000), although DeLucia et al (2003) estimated stand-level bryophyte LAI in a New Zealand forest. In most vascular plant systems, LAI strongly inXuences energy, water and carbon dioxide exchange between terrestrial ecosystems and the atmosphere and is tightly coupled with photosynthesis, litterfall, microclimate and productivity (Gower et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Lichens recover rapidly but then remain active only briefly, while, at the other extreme, many mosses recover slowly but then remain active longer (Green et al 2011a;Kappen and Valladares 2007;Proctor 2004;Zotz et al 2000;Zotz and Rottenberger 2001). The greater time and thallus water content required by mosses to recover full activity, plus the enhanced respiratory activity after rehydration (Dilks and Proctor 1976;Farrar and Smith 1976;Schlensog et al 2004) means that partial hydration followed by rapid drying, as found in hot desert environments, can lead to damage and death (Coe et al 2012(Coe et al , 2014Barker et al 2005;Stark et al 2011).…”
Section: Recovery From Desiccationmentioning
confidence: 99%
“…Water loss in bryophytes is controlled by canopy structural properties (Proctor, 1980(Proctor, , 1982Zotz et al, 2000;Rice and Schneider, 2004), as opposed to vascular plants, in which leaf stomata regulate water fluxes. As a poikilohydric plant, a bryophyte-more specifically the water vapour partial pressure of the plant body-is always in equilibrium with ambient humidity (Green and Lange, 1994); this lack of active control over plant water status implies fundamentally different ecosystemlevel dynamics as well (Longton, 1992;Turetsky, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…As a poikilohydric plant, a bryophyte-more specifically the water vapour partial pressure of the plant body-is always in equilibrium with ambient humidity (Green and Lange, 1994); this lack of active control over plant water status implies fundamentally different ecosystemlevel dynamics as well (Longton, 1992;Turetsky, 2003). The morphology of the bryophyte canopy influences the development of a boundary layer adjacent to the plant surface (Campbell and Norman, 1998), which in turn greatly influences the plant water and carbon budgets (Zotz et al, 2000;Rice et al, 2001). Bryophyte water status is a function of factors spanning a wide range of scales: cell turgidity, osmotic potential, local hydrology, distance from the water table and thallus water content (Dilks and Proctor, 1979;Hayward and Clymo, 1982;Proctor, 1982Proctor, , 2000aProctor and Tuba, 2002).…”
Section: Introductionmentioning
confidence: 99%